Latino Values in the Context of Palliative Care: Illustrative Cases From the Family Focused Grief Therapy Trial. (May 2013) - Gaudio, F. Del; Hichenberg, S.; Eisenberg, M.; Kerr, E.; Zaider, T. I.; Kissane, D. W.
Background: Clinicians meet a variety of ethnicities among patients and families in hospice programs. This article focuses on Latino families. Methods: Within a controlled trial of family therapy in the context of palliative care, 17 families identified as Hispanic. Five were examined qualitatively herein. Results: A synopsis of each family's narrative is presented here. Patterns of strong family loyalty ( Familismo ), the gender roles of Machismo and Marianismo, the importance of family tradition, expectations about caregiving, and the place of faith and religion emerged as prominent and able potentially to impact on the therapy. Conclusions: Family therapists need to be thoughtful about cultural issues as they strive to support families.